Nitrogen deposition in forests: Statistical modeling of total deposition from throughfall loads - Braun, Sabine; Ahrends, Bernd; Alonso, Rocio; Augustin, Sabine; García-Gómez, Hector; Hůnová, Iva; Karlsson, Per Erik; Karlsson, Gunilla Pihl; Schmitz, Andreas; Thimonier, Anne (Frontiers in Forests and Global Change, 2022)
Nitrogen (N) gradient studies in some cases use N deposition in throughfall as measure of N deposition to forests. For evaluating critical loads of N, however, information on total N deposition is required, i.e. the sum of estimates of dry, wet and occult deposition. The present paper collects a number of studies in Europe where throughfall and total N deposition were compared in different forest types. From this dataset a function was derived which allows to estimate total N deposition from throughfall N deposition. At low throughfall N deposition values, the proportion of canopy uptake is high and thus the underestimation of total deposition by throughfall N needs to be corrected. At throughfall N deposition values >20 kg N ha 1 yr 1 canopy uptake is getting less important.